2005
DOI: 10.1111/j.1574-0864.2005.00074.x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of food security in Southern Ethiopia at the household level

Abstract: In the early 1980s, a paradigm shift occurred in the field of food security, following Amartya Sens (1981) claims that food insecurity is more of a demand concern, affecting the poor's access to food, than a supply concern, affecting availability of food at the national level. Despite the wide acceptance of Sen's thinking, many controversies including the relative importance of supply-side versus demand-side variables in causing and solving food insecurity have remained in academic and policy circles. This stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
93
2
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(111 citation statements)
references
References 10 publications
13
93
2
3
Order By: Relevance
“…The results from the FGDs held in the study area show that households sold their livestock and livestock product to purchase food for family consumption during drought and crop failure problem. Holding other explanatory variables constant, the odds ratio in favor of food security decreases by a factor of 0.6178 when the distance in hours of walk increases by 1 h. Also, other findings confirm the result of this study [31,64].…”
Section: Assessment Of Household Food Security In the Face Of Climatesupporting
confidence: 81%
“…The results from the FGDs held in the study area show that households sold their livestock and livestock product to purchase food for family consumption during drought and crop failure problem. Holding other explanatory variables constant, the odds ratio in favor of food security decreases by a factor of 0.6178 when the distance in hours of walk increases by 1 h. Also, other findings confirm the result of this study [31,64].…”
Section: Assessment Of Household Food Security In the Face Of Climatesupporting
confidence: 81%
“…Using availability of food in the household as proxy indicator for food security, they found that the most significant factors affecting household food security were: the educational level of the spouse and that of the household head, size of farm land, availability of household assets including livestock, peace and security. Beside household endowments such as land (Feleke et al 2005) and proximity to food markets (Abay and Hirvonen 2016), Negatu (2004) reports that livelihood diversification strategies such as livestock rearing, growing cash crops, and engagement in trading are important factors for achieving household food security.…”
Section: Used With Permission From the International Food Policy Resementioning
confidence: 99%
“…In order to address the problem of decreased access to food and limited availability of food in resource-limited contexts, identifying those at highest risk for food insecurity is critical for programme planning (11) . Research in other developing countries has identified household size (12) , maternal age (13) and educational status (13) , as well as the presence of social support, as being important determinants of food insecurity (14) . Information on proven risk factors can aid in targeting programmes specifically aimed at reducing household food insecurity within unique socio-cultural contexts.…”
mentioning
confidence: 99%